Análisis de los ingresos en el Gobierno Autónomo Descentralizado Municipal del cantón Alfredo Baquerizo Moreno (Jujan) año 2020 - Castro Eguez, Sleyter Javier (2021)
This article analyzes the financial aspects in the municipal GAD of Jujan in which we will analyze the items that affect the collection of income within the institution; we will also analyze those aspects that allow the development of the company, currently it has been affected due to the large indebtedness that it maintains during the 2019-2020 period. We will use tools such as the interview to deal in depth on the subject since, through open questions; the officials express themselves a little more, thus allowing us to study each of their problems.